Biomechanical report for the IAAF World Championships London 2017 hammer throw women's - Dinsdale, A.; Thomas, A.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The women`s hammer final took place on the night of August 7th in good weather conditions. Coming into the final, Anitia Wlodarczyk from Poland was the favourite as the world leader in 2017, current world record holder and Olympic Champion of 2016. After the first three rounds, Zheng Wang from China led the competition with a 75.98 m throw. Subsequently, Wlodarczyk seized the gold medal by throwing an impressive 77.39 m in the fourth round and then bettering this in the fifth round with a throw of 77.90 m. Wang was already assured of the silver medal going into her final throw, whereby she produced her best throw of the night measured at 75.98 m. Malwina Kopron from Poland secured the bronze medal with her first throw of the evening measured at 74.76 m, however she was unable to better this in the subsequent five rounds of the competition. (Attention! registration on the IAAF site is required for downloading)